Історіографія народної прози Західного Полісся - Давидюк, Лілія; Davydyuk, Liliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто проблему зібрання, систематизації та видання фольк- лорної прози Західного Полісся. Матеріалом для дослідження стали праці вітчизняних і закордонних фольклористів, які ще з початку ХІХ ст. фіксували й публікували у своїх розвідках прозові зразки західнополіської народної творчості.Article accommodate consider the important issues of modern folklore – problems fixing and publications prosaic folk samples from the region of Western Polissya.The material for analysis was the work of domestic and foreign folklorists, which were published the folk narratives of the studied ethno-cultural region. The aim of the study delivered to analyze the specifics and fixing prosaic Western Polissya's samples folklore scientists at different historical stages. The study found the overall trends of the regional operation of oral narrative traditions of Western Polissya, since the nineteenth century to the present time. It is shown that the history of the collection and publication of regional folk tales passed a long way – from fragmentary commits to purposeful publications. Indicated on the main directions of the necessary followup work with the available archival funds folk narratives.
The Historiography of Folk Prose of Western Polissya
Keywords: фольклорна проза; Західне Полісся; західнополіські наративи; усна традиція; народні оповідання; folk prose; Western Polissya; narratives of Western Polissya; oral tradition; folk tales